Bathhouse - Pablo, Crisaldo; Raganit, Rowena; Alcantara, Jet; Ranay, Andoy; Pumaloy, Rey (ProGay Philippines, 2006)
Bathhouse seeks to expose the cruel world that gays have waved within the dark stingy walls of quasi-bathhouses in the Philippines. The story revolves around the lives of men who frequent the seedy bathhouse 'Klub Hombre' where you have to be masculine, attractive, huge in order to e accepted to the exclusive club.